Recidivism of Child Crime in Indonesia - Ma'aly, Moh. Haizul; Hidayati, Rahmatul; Parmono, Budi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
This study began with children who commit deviant acts often showing a bad attitude in the eyes of society and the government. They are often stigmatized as naughty children or perpetrators of criminal acts. Children who commit crimes must also be punished, but the punishment given is different from the punishment given to adults. The purpose of this study is to find out, understand, and analyze both in terms of regulations, forms and sanctions for children who commit repeated crimes. The research method used is normative legal research with a statutory approach, namely Law Number 1 of 1946 concerning the Criminal Code and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and a conceptual approach. The technique of collecting legal materials in this study uses literature studies while the legal material analysis technique used in this study is the descriptive analysis method. The results of this study indicate that in the SPPA Law concerning the imposition of sanctions on children who commit repeat crimes, there is a legal vacuum so that when judges handle cases of children who commit repeat crimes, the sanctions are returned to the Criminal Code, which sanctions are in the form of imprisonment that is heavier than before, namely plus one third. Therefore, the legislators in this case failed to formulate a norm in the formulation of the crime.